IMPLEMENTASI PERANGKAT PEMBELAJARAN BERBASIS MASALAH GUNA MENGEMBANGKAN KECERDASAN EMOSIONAL MAHASISWA MATEMATIKA - Armiati Armiati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Emotional intelligence is recognized as an ability to participate influential in determining one's success. This paper will discuss the research results relating to the development of emotional intelligence of students of mathematics. Based on survey results revealed the existence of positive changes in emotional intelligence of students after attending a course using problem-based learning tools.